Health Care System Application (Good Care) Android-Based at Primary Health Care (Case Study at Clinic of Wijaya Kusuma) - Oliva Prasastin; Anggi Napida; Nabilatul Fanny (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
The development of information systems is currently experiencing very rapid development which we now recognize as the era of digitalization, one of which is in the field of health services. Primary healthcare is a type of medical health service that provides health services to individuals at the first level health service. The problem that most often arises is related to the registration system which is still done manually by recording in the registration book, thereby allowing the risk of errors occurring and the process of searching for visit data taking a long time. This research aims to improve better service for visits so it is necessary a good, systematic and integrated data handling and processing in a developing service system, even at the level of independent health service practice. This research method uses Field Observation, Library Research, Interviews, Study Research Literature (Research Literature Study), System Design, System Implementation and Testing. Application system from syntax errors and functionally produces functions as expected. The health service system application (Good Care) has been tested and can be used so that it can increase the effectiveness and efficiency of health services at the independent doctor's practice at Clinic of Wijaya Kusuma.